2009
DOI: 10.1074/jbc.m806898200
|View full text |Cite
|
Sign up to set email alerts
|

The Cholinesterase-like Domain, Essential in Thyroglobulin Trafficking for Thyroid Hormone Synthesis, Is Required for Protein Dimerization

Abstract: The carboxyl-terminal cholinesterase-like (ChEL) domain of thyroglobulin (Tg) has been identified as critically important in Tg export from the endoplasmic reticulum. In a number of human kindreds suffering from congenital hypothyroidism, and in the cog congenital goiter mouse and rdw rat dwarf models, thyroid hormone synthesis is inhibited because of mutations in the ChEL domain that block protein export from the endoplasmic reticulum. We hypothesize that Tg forms homodimers through noncovalent interactions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 43 publications
2
38
0
Order By: Relevance
“…We previously showed that ChEL can be folded and exported as an independent secretory protein (15), yet ChEL is strongly implicated in Tg conformational stability and dimerization, allowing for Tg export from the ER (18). If we wish to understand the mechanism for Tg maturation and export, we must dissect the way in which local domain-specific folding (and folding defects) impact(s) on regional interactions within the larger Tg polypeptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously showed that ChEL can be folded and exported as an independent secretory protein (15), yet ChEL is strongly implicated in Tg conformational stability and dimerization, allowing for Tg export from the ER (18). If we wish to understand the mechanism for Tg maturation and export, we must dissect the way in which local domain-specific folding (and folding defects) impact(s) on regional interactions within the larger Tg polypeptide.…”
Section: Discussionmentioning
confidence: 99%
“…Mouse monoclonal anti-HA epitope was from Covance (Princeton, NJ). Rabbit polyclonal anti-Tg (containing antibodies against epitopes at both N-and C-terminal regions of the protein) has been described previously (17 Mutagenesis of Mouse Tg-cDNAs encoding secretory ChEL and truncated Tg regions I-II-III (L2169X) and secretory ChEL and ChEL-myc have been described previously (14,15,18). Other constructs described in this paper were made using the QuikChange site-directed mutagenesis kit (Stratagene) using following the mutagenic primers paired with their complements: Tg-Q2139X and Q2139X in secretory II-III (5Ј-GGT-TGTGAGATGTGTGTTCTACCCTGATATATAGTAATG-CATACACAGTCTACGGAGCC-3Ј); C1973S in secretory II-III-HA (5Ј-CCAATGGGTTCTTTGAGAGTGAGCGGCT-CTGTGACAGGG-3Ј); Tg-E1192X (5Ј-GGTAGGCACCCA-GCCTGCCTGTTAAAGCCCACAGTGTCCACTGCC-3Ј); Tg-A1435X (5Ј-CCCAACCACCAGACAGGATTGACTG-GGCTGTGTGAAATGCCC-3Ј); Tg-Q1509X (5Ј-CCAGA-ATGGTCAGTACTAAGCCAGCCAGAAGAACAGGG-3Ј).…”
Section: Methodsmentioning
confidence: 99%
“…Mutagenesis of Mouse Tg-cDNAs encoding secretory ChEL and truncated Tg regions I-II-III and secretory ChEL and ChEL-Myc have been described previously (17,25,26). Other constructs described in this study were made using the QuikChange site-directed mutagenesis kit (Agilent Technologies, Inc.) using following the mutagenic primers paired with their complements: Tg-C175X (5Ј-GCCTGTCCAGGAACAGAAGC-TCATTTCCGAAGAGGACCTGTGATTTGATCTGATCC-3Ј); Tg-R277X (Myc-tagged, 5Ј-CTGGCAGATTTGAGCAGAA-GCTTATCTCTGAAGAAGACCTGTAGGCTGCCACCAGA-TTTG-3Ј); Tg-P279X (Myc-tagged, 5Ј-GGCAGATTTCGGTG-CGAGCAGAAGTTGATATCAGAAGAGGACCTTTAGACC-AGATTTGG-3Ј); Tg-G293X (Myc-tagged, 5Ј-GCCACCAGAT-TTGAGCAGAAGCTTATCTCTGAAGAAGACCTGTAGGC-TGCCACCAG-3Ј); Tg-A340X (5Ј-GGGCAGCCTCCATCTTG-CTAGTGAGATCAGTCATGTGCCTTGG-3Ј); Tg-C388S (5Ј-GGTGTCAGATCGGACACATCCTCCCCACCCAGAATCA-AGG-3Ј); Tg-C1245R (5Ј-TGCTGACTCTCCAGGCTACGAA-TCAGTGGCCC-3Ј); Tg-C1489S (5Ј-GGAGCTTTCAGCAAA-ACCCATTCTGTCACTGACTGTCAGAAGAATGAGG-3Ј); Tg-C1973S (5Ј-CCAATGGGTTCTTTGAGAGTGAGCGGCT-CTGTGACAGGG-3Ј); and Tg region I (Tg-A1435X, 5Ј-CCCAACCACCAGACAGGATTGACTGGGCTGTGTGAAA-TGCCC-3Ј).…”
Section: Methodsmentioning
confidence: 99%
“…Concomitant with resolution of these complexes, and thereafter, there is extensive intramolecular disulfide bond maturation within internal repeat domains of the molecule (16). The oxidation of Tg monomers culminates in a transition from the "D" to oxidized "E" isoform that precedes homodimerization (17), which helps to satisfy "ER quality control" requirements that control efficiency and rate of Tg export from the ER (18).…”
mentioning
confidence: 99%
“…Type 1 repetitive units present in the TG sequence have been suggested to act as binders and reversible inhibitors of the proteases implicated in TG processing (Molina, Pau, & Granier, 1996). The ACHE-homology domain is essential for protein dimerization, which plays an important role in the normal conformational maturation and intracellular transport of TG (Lee, Wang, Di Jeso, & Arvan, 2009). Cysteine residues are required in the tertiary structure of TG (Lee, Wang, Di Jeso, & Arvan, 1993).…”
Section: Discussionmentioning
confidence: 99%